The Human River: The Playful Reclamation of Ecological History and Public Space - Forsberg, Liz (UnderCurrents: Journal of Critical Environmental Studies, 2007)
On a Sunny Sunday Afternoon You are sitting on your porch steps under the dappled sunlight of the old maples that line your Toronto street, enjoying a beautiful fall day. Out of the corner of your eye, you notice a steady stream of people walking out of the alleyway across the street from your house. What is this procession all about?